2012
DOI: 10.1128/jb.00095-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Rahnella sp. Strain Y9602, a Gammaproteobacterium Isolate from Metal- and Radionuclide-Contaminated Soil

Abstract: dRahnella sp. strain Y9602 is a gammaproteobacterium isolated from contaminated subsurface soils that is capable of promoting uranium phosphate mineralization as a result of constitutive phosphatase activity. Here we report the first complete genome sequence of an isolate belonging to the genus Rahnella. R ahnella sp. strain Y9602 is a gammaproteobacterium isolated from a mixed-waste-contaminated subsurface (i.e., low pH and high concentrations of nitrate, heavy metals, and radionuclides) at the U.S. Departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…These eight species contributed to the existing diversity of Rahnella with isolations of Rahnella victoriana, Rahnella variigena and Rahnella inusitata from bleeding cankers of oak; R. victoriana, R. variigena and R. woolbedingensis from asymptomatic alder and walnut; Rahnella bruchi from the gut of the Agrilus biguttatus beetle; Rahnella aceris and Rahnella laticis from sap of Acer pictum and Rahnella contaminans as a contaminant from MRSA agar plates [5][6][7]. In addition to their isolation from the natural environment, Rahnella species have been linked to nitrogen-fixation [8], metal and radionuclide sequestration [9] and biological control [10]; and more recently as possible pathogens of oak [11], poplar [12] and onion [13].…”
mentioning
confidence: 99%
“…These eight species contributed to the existing diversity of Rahnella with isolations of Rahnella victoriana, Rahnella variigena and Rahnella inusitata from bleeding cankers of oak; R. victoriana, R. variigena and R. woolbedingensis from asymptomatic alder and walnut; Rahnella bruchi from the gut of the Agrilus biguttatus beetle; Rahnella aceris and Rahnella laticis from sap of Acer pictum and Rahnella contaminans as a contaminant from MRSA agar plates [5][6][7]. In addition to their isolation from the natural environment, Rahnella species have been linked to nitrogen-fixation [8], metal and radionuclide sequestration [9] and biological control [10]; and more recently as possible pathogens of oak [11], poplar [12] and onion [13].…”
mentioning
confidence: 99%
“…The results also indicated that the ANI and DDH values between ATCC 33071 T and other R. aquatilis strains (including HX2, ZF7, Y9602) were below 95 and 70%, respectively, and this was consistent with the previous report showing that the ANI value between R. aquatilis strains ZF7 and ATCC 33071 T was only 92.9% ( Yuan et al, 2020 ). Previous studies indicated that strain ZF7, HX2 and Y9602 were both isolated from soil ( Guo et al, 2012 ; Martinez et al, 2012a ), while ATCC 33071 T was isolated from drinking water ( Martinez et al, 2012b ), so, it may suggest that the genetic evolutionary distance could be associated with the habitat and adaptation. All five Rahnella strains harbored one or more plasmids, which could be related to genetic evolution, based on the previous report that 19% of strains in the genus Rahnella were plasmid-containing and had highly homologous regions for the same species ( Rozhon et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genes present in the three Rahnella genomes available at the time, R. aquatilis ATCC 33071, Rahnella sp. Y960 (Martinez et al, ), and R. aquatilis HX2 (Guo et al , ), but not in other available genomes, were used to search the NCBI Whole Genome Shotgun database and filtered based on length (at least 300 bp). Putative genes that appeared to be unique to the three sequenced Rahnella strains were considered good target regions for designing specific primers.…”
Section: Methodsmentioning
confidence: 99%